2021
DOI: 10.1200/jco.2021.39.15_suppl.1063
|View full text |Cite
|
Sign up to set email alerts
|

Rintodestrant (G1T48), an oral selective estrogen receptor degrader, in combination with palbociclib for ER+/HER2– advanced breast cancer: Phase 1 results.

Abstract: 1063 Background: Rintodestrant, a potent, oral selective estrogen receptor degrader, competitively binds and degrades the estrogen receptor (ER), thus blocking ER signaling in tumors resistant to other endocrine therapies (ET). Results from parts 1 and 2 dose-escalation/expansion indicate that once-daily (QD) rintodestrant has a favorable safety profile and antitumor activity in patients (pts) with heavily pretreated ER+/HER2– advanced breast cancer (ABC), including those with ESR1 variants (Aftimos et al. SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…However, among a larger group of 67 patients treated with monotherapy, 20 patients were on study >24 weeks but only 3 patients experienced partial response (PR), with a median PFS of 2 months. Similar response rates were observed when G1T48 was combined with palbociclib [54,55]. The toxicity profile appears to be favorable, with <10% of patients experiencing grade 1-2 nausea, vomiting, and neutropenia.…”
Section: Serds With Acrylic Acid Side Chainssupporting
confidence: 57%
“…However, among a larger group of 67 patients treated with monotherapy, 20 patients were on study >24 weeks but only 3 patients experienced partial response (PR), with a median PFS of 2 months. Similar response rates were observed when G1T48 was combined with palbociclib [54,55]. The toxicity profile appears to be favorable, with <10% of patients experiencing grade 1-2 nausea, vomiting, and neutropenia.…”
Section: Serds With Acrylic Acid Side Chainssupporting
confidence: 57%
“… 32 Rintodestrant (G1T48) was tested in a phase I trial in pre-treated ER-positive, HER2-negative advanced breast cancer patients that had not received a CDK4/6i, and was found to be effective, including in patients with ESR1 mutations. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies found no interaction between palbociclib and camizestrant, 50 , 53 giredestrant 64 or rintodestrant. 63 An interaction between amcenestrant and palbociclib is possible, with amcenestrant having a moderate cytochrome P450 3A4 induction effect and reducing palbociclib exposure in a dose-dependent manner, hence the recommended dose for amcenestrant is 200 mg in combination with palbociclib, compared with 400 mg as monotherapy. 65 Several oral SERDs are undergoing evaluation in combination with abemaciclib, but no results are reported yet.…”
Section: Oral Serd With Cdk4/6 Inhibitor Early Phase Trialsmentioning
confidence: 99%
“…The objective response rates (ORRs) and clinical benefit rates (CBRs) reported for combination therapy have been higher than for oral SERD monotherapy, and even complete responses have been seen with the combination of high-dose giredestrant and palbociclib, 61 and with camizestrant plus palbociclib. 53 Anti-tumor activity has also been evident as reduction in the ESR1 mutation allele frequency or ctDNA levels with treatment, 50,[61][62][63][64] and as downregulation of ER, PR and Ki67 in paired pre-and on-treatment tumor biopsies in early stage breast cancer. 61,64 The combinations have been well tolerated and like AI plus CDK4/6 inhibitor therapy, the most frequent side effect of oral SERD and CDK4/6 inhibitor therapy has been neutropenia.…”
Section: Oral Serd With Cdk4/6 Inhibitor Early Phase Trialsmentioning
confidence: 99%